ASSOCIATION BETWEEN AEROALLERGEN SENSITIZATION AND THE SEVERITY OF ASTHMA IN PEDIATRIC PATIENTS - Vivin Detriana; Agung Prasetyo Wibowo; Muchammad Fahrul Udin; Ery Olivianto; Wisnu Barlianto; HMS. Chandra Chandra (UNEJ e-Proceeding)
Asthma is one of the most common chronic diseasesin childhood, with increasing prevalence in the past3 decades (Nievas et al, 2013). The prevalence ofasthma in the world is approximately 7.2% (6%adults and 10% children).There are variations in the prevalence and mortalityof asthma. WHO estimates that there are currently250,000 deaths due to asthma. It is leading cause ofchildhood hospitalization and school absenteeism.Asthma is more prevalent in boys in the first years oflife, but in adolescents it predominates amongfemale subjects. Asthma affects minority and lowincomegroups disproportionately (Herzog et al,2011; Rahajoe, 2013).In Indonesia, Asthma is the top ten causes ofmorbidity and mortality. The study data ofhousehold health survey in 1986 in various provincesin Indonesia showed asthma ranks 5th of 10thcauses of morbidity. In 1992 Household HealthSurvey, asthma, chronic bronchitis and emphysemaas 4th cause of death in Indonesia (5.6%). In 1995,the prevalence of asthma in Indonesia approximately13/1000, compared with chronic bronchitis is11/1000 and pulmonary obstruction is 2/1000(Guidelines for Diagnosis and Management ofAsthma In Indonesia, 2013)Asthma is a heterogeneous disorder in children thatis characterized by recurrent airway obstruction,bronchial hyper-responsiveness, and airwayinflammation. (Herzo et al, 2011).The pathophysiologic basis of asthma is not wellunderstood. It appears to have a complex,multifactorial etiology which results from aninterplay of many hereditary factors and a numberof environmental factors. Bronchial biopsies frompatients with even mild asthma have evidence ofchronic inflammation, and cytokines and othermediators of inflammation are found in bronchialwashings from asthma patients. Some families aremore prone to development of allergies, and there isa well-known association between allergies andasthma. This suggests a genetic predisposition, but itappears that a number of genes are involved.Proceeding ICMHS 2016 ISBN 978-602-60569-3-1127Figure 1. Pathophysiology of astmaSource: Busse W. & Lemanske R: N. Engl. J. Med.2001;344(5):350-362Asthma attacks is vary from mild to severe and lifethreatening. The various factors which can triggerasthma attacks, such as exercise, allergens,infections, sudden changes in air temperature, orexposure to respiratory irritants such as cigarettesmoke and others. (Rahajoe, 2013)Aeroallergen sensitization is a risk factor in thedevelopment of childhood asthma. Aeroallergensensitization occurs in most patients with asthmaand is noted in a high percentage of patients withmild and moderate asthma. The percentage of thosethat are atopic with severe asthma appears less, butstill approximates the percent seen in patients withmild and moderate asthma. The most commonlyimplicated allergens are house dust mite (HDM),cockroach, and furred animals. Aeroallergensensitization can be evaluated using skin testing. (Rajet al, 2013)House dust mites are arachnids that are microscopicin size (~0.33mm long). They are found in dust andproducts with woven material or stuffing such asmattresses, pillows, stuffed animals, and bedding.Their life cycle from egg to adult takes 3 to 4 weeksand they live for 6 to 8 weeks. Females produce 40to 80 eggs during this time.It has been shown that dust mite exposure in earlychildhood is an important determinant in asthmadevelopment. Sporik et al. showed that 16 of 17children with asthma were sensitized to dust mite.urther, the higher the level of dust mite exposure at1 year old, the earlier the first episode of wheezingoccurred. The relative risk of asthma was almost 5-times greater in the subjects who were exposed tohigh levels of dust mite allergen (>10 μg/g) (Baxi etal, 2010)They demonstrated that early exposure to housedust mite was associated with an increased risk ofasthma and late onset wheezing. They followed agroup of 440 children from birth to 7 years andfound that children exposed to high levels of dustmite allergen in their bed at 2 to 3 months old had a3-fold increase in the odds of asthma at age 7 yearsold compared with those exposed to low level dustmite allergen (Baxi et al, 2010)Skin prick testing (SPT) is an easy, cost-effective andconvenient approach to identify sensitization toallergens. SPT detects the presence of allergenspecific IgE bound to mast cells by eliciting mast celldegranulation to the specific allergen being tested(Raj et al, 2013).The purpose of this study was to determine theassociation of aeroallergen sensitization and theseverity of asthma in pediatric patients.